A systematic review on the role of mitochondrial dysfunction/disorders in neurodevelopmental disorders and psychiatric/behavioral disorders - Pinto Payares, Daniela V.; Spooner, Logan; Vosters, Jennifer; Dominguez, Samantha; Patrick, Lauren; Harris, Ann; Kanungo, Shibani (Frontiers in Psychiatry, 2024)
Introduction Mitochondrial diseases are known inborn errors affecting energy metabolism and are as common as chronic diseases such as diabetes, affecting approximately 1 in 5,000 people. The role of mitochondrial diseases/dysfunction has been highlighted in neurodevelopmental disorders like ASD, ADHD, intellectual disability, and speech delay, as well as various psychiatric conditions. Neurodevelopmental disorders are increasingly recognized as having behavioral and psychiatric symptoms. Our study aimed to investigate reports of mitochondrial disorders, noting neurodevelopmental disorders and psychiatric/behavioral conditions. Methods This was done through a systematic review of literature from PubMed/MEDLINE, Scopus, and Cochrane Library up to November 2022. Results We found 277 publications, of which 139 met the inclusion criteria. We mostly found review articles with mention of mitochondrial dysfunction/disorder in relation to ASD with brief mentions of psychiatric/behavioral comorbidities. Discussion This suggests a need for broader research efforts beyond ASD to understand the relationship between mitochondrial disorder or dysfunction and various neurodevelopmental and psychiatric/behavioral comorbidities.